Smallholder irrigation and poverty reduction in developing countries: a review - Norman Mupaso; Godswill Makombe; Raymond Mugandani (Elsevier, 2023)
Several studies have been conducted on the impacts of smallholder irrigation on food security, agricultural productivity, livelihoods, and poverty. However, little attention has been placed on the nexus between smallholder irrigation and poverty reduction. This study intends to close this gap by identifying and reviewing contemporary published evidence to examine the nexus be- tween smallholder irrigation and poverty reduction in developing countries in general and Zimbabwe in particular. A systematic review of literature was conducted. The AGRICOLA, PubAG and Google Scholar databases were used to search for relevant literature. A multi-stage screening process was used to select relevant literature. The literature reviewed included research publi- cations in peer-reviewed journals, dissertations and reports from world institutions published between 1994 and 2021. The findings show that there are inconsistencies in terms of the contribution of smallholder irrigation to household food security, livelihoods, and poverty reduction. This could be attributed to the methodological and contextual differences. Despite the inconsistencies, it was noted that investments in smallholder irrigation remain a key strategy to enhance agricultural productivity, food security, and livelihoods and reduce poverty in rural communities. Therefore, the study recommends that policies supporting investments in small- holder irrigation development and rehabilitation should be encouraged in developing countries to reduce poverty.